Religious Moderation Representation on Nu Online Instagram Account; Teun A. Van Dijk’s Critical Discourse Analysis - Mukminin, Muhamad Saiful; Yafuz, Labiq (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2024)
The present research employs a descriptive qualitative approach to analyze religious moderation in the content of the Instagram account @nuonline_id. The research data consists of four posts that contain elements of religious moderation, focusing on national commitment, tolerance, anti-violence, and acceptance of tradition. The theoretical approach used is Teun A. Van Dijk's critical discourse analysis, which allows the researcher to explore the ideologies and values embedded in the texts. The research findings highlight four aspects of religious moderation: national commitment, tolerance, anti-violence, and acceptance of tradition. This study concludes that @nuonline_id serves as a source of information and a catalyst for positive change in society by emphasizing the values of moderation in religious practice. The recommendations of this study include the need for further research on the role of social media in promoting the values of religious moderation in Indonesia.   Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk menganalisis moderasi beragama dalam konten Instagram @nuonline_id. Data penelitian terdiri dari empat postingan yang mengandung unsur moderasi beragama, dengan fokus pada komitmen nasional, toleransi, anti-kekerasan, dan penerimaan tradisi. Pendekatan teori yang digunakan adalah analisis wacana kritis Teun A. Van Dijk. Hasil penelitian menyoroti empat aspek moderasi beragama yaitu komitmen nasional, toleransi, anti-kekerasan, dan penerimaan tradisi. Penelitian ini menyimpulkan bahwa @nuonline_id berfungsi sebagai sumber informasi dan katalis perubahan positif dalam masyarakat dengan menekankan nilai-nilai moderasi dalam praktik beragama. Rekomendasi penelitian ini mencakup perlunya studi lebih lanjut tentang peran media sosial dalam mempromosikan nilai-nilai moderasi beragama di Indonesia.